CYTOPROTECTIVE THERAPY POTENTIAL IN PATIENTS WITH CHRONIC COR PULMONALE - S. A. Surotkina; A. A. Kotlyarov; N. M. Selezneva; E. N. Efremova (Российский кардиологический журнал)
The study investigated effectiveness and safety of a cytoprotector mexicor in patients with chronic cor pulmonale (CCP). All participants (n=56; age 38-80 years) were divided into four groups. Group I (n=16) received a standard pulmonary therapy, while Group II (n=20) also received mexicor (300 mg/d intravenously, for 10 days), Group III (n=10) received a standard therapy plus verapamil (80-240 mg/d for 10 days), and Group IV (n=11) was administered intravenous mexicor (300 mg/d) plus verapamil (80-240 mg/d) for 10 days. All participants underwent daily measurement of blood pressure and heart rate, 6-minute walk test, spirography, Holter ECG monitoring, echocardiography, and colour Doppler ultrasound of common and internal carotid arteries. Adding mexicor to the standard therapy of CCP patients increased treatment effectiveness for the leading pathology, as well as for co-morbidities (heart failure, cardiac arrhythmias). Additionally, in these patients, mexicor improved effectiveness and safety of verapamil treatment, increasing its antihypertensive and antiarrythmic activity and reducing its negative effects on intracardiac hemodynamics.